2011
DOI: 10.1159/000327249
|View full text |Cite
|
Sign up to set email alerts
|

Weight Outcomes Audit for 34,271 Adults Referred to a Primary Care/Commercial Weight Management Partnership Scheme

Abstract: Objective: This project audited rate and extent of weight loss in a primary care/commercial weight management organisation partnership scheme. Methods: 34,271 patients were referred to Slimming World for 12 weekly sessions. Data were analysed using individual weekly weight records. Results: Average (SD) BMI change was –1.5 kg/m2 (1.3), weight change –4.0 kg (3.7), percent weight change –4.0% (3.6), rate of weight change –0.3 kg/week, and number of sessions attended 8.9 (3.6) of 12. For patients atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
106
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 25 publications
12
106
3
Order By: Relevance
“…These data are consistent with the findings from the National Weight Control Registry, which suggest that the maintenance of weight loss is not easy and often takes several repeated attempts before people learn to navigate to and remain at a healthy body weight [6,18]. Information on why people fail to lose weight or fail to maintain weight loss is less common than descriptions of weight loss and maintenance behaviours [11,16,28,32,33]. This is despite the observation by Jeffrey et al that the increasing prevalence of obesity and high-self reported rates of dieting in the general population suggest attempts at weight loss are being offset by failures [10].…”
Section: Weight History and Previous Attempts At Weight Losssupporting
confidence: 83%
See 1 more Smart Citation
“…These data are consistent with the findings from the National Weight Control Registry, which suggest that the maintenance of weight loss is not easy and often takes several repeated attempts before people learn to navigate to and remain at a healthy body weight [6,18]. Information on why people fail to lose weight or fail to maintain weight loss is less common than descriptions of weight loss and maintenance behaviours [11,16,28,32,33]. This is despite the observation by Jeffrey et al that the increasing prevalence of obesity and high-self reported rates of dieting in the general population suggest attempts at weight loss are being offset by failures [10].…”
Section: Weight History and Previous Attempts At Weight Losssupporting
confidence: 83%
“…There has recently been a cluster of publications on the effectiveness of commercial weight management organisations (CWMOs), which have become a mainstream source of weight management solutions to a significant proportion of the general population [23][24][25][26][27][28]. The purpose of this study was to conduct an initial survey of members from a British CWMO who participated for a minimum of three months and who have on average lost >15 kg in weight.…”
mentioning
confidence: 99%
“…Audit data show the increasing use of referral schemes in the United Kingdom, 8,9 and 2 recent randomized controlled trials provide evidence to support this approach. 10,11 We recently published the results of an international randomized controlled trial in which 772 participants from 3 countries (United Kingdom, Australia, and Germany) were recruited by their primary care physician and randomized to receive 12 months' free membership of a commercial program, eg, Weight Watchers, or standard care in general practice.…”
Section: W Eigh T Los S Int Erv Ent Ionmentioning
confidence: 99%
“…When services were not sex-specific, men comprised only 10.7% of 34,271 adults referred from primary health care to one UK commercial weight loss programme (Slimming World) [7], and 10.5% of 29,326 adults referred to a different commercial programme (Weight Watchers) [8]. Thus UK figures suggest men may be even less likely than women to attend commercial weight loss programmes than programmes provided by the National Health Service (NHS).…”
Section: Introductionmentioning
confidence: 99%